CAN INCLUSIVE EDUCATION GUARANTEE INCLUSIVE GROWTH IN INDIA? REIMAGINING EDTECH FOR VIKSIT BHARAT@2047 - Dash, Swaraj; Nath, Bibha Rani; C, Blessy Paul (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Education Technology (EdTech) has emerged as a transformative instrument for advancing digital empowerment, educational inclusion, and inclusive growth in India, particularly in the post-pandemic era. The rapid expansion of online learning platforms, artificial intelligence (AI)-enabled educational tools, mobile-based learning applications, and virtual classrooms has significantly reshaped the country’s educational ecosystem. Despite these advancements, deep structural inequalities continue to widen the urban–rural learning divide, limiting equitable access to quality education and digital opportunities. Against the broader developmental vision of Viksit Bharat@2047, this paper critically examines how EdTech can serve as a pathway for bridging educational disparities and fostering inclusive socioeconomictransformation in India. Drawing upon secondary data, policy documents, government reports, and existing scholarly literature, the study analyses the key barriers affecting rural educational inclusion, including inadequate digital infrastructure, affordability constraints, low digital literacy, gender disparities, linguistic exclusion, and socioeconomicinequalities. The paper further evaluates major government initiatives such as Digital India, PM eVIDYA, SWAYAM, DIKSHA, and BharatNet, alongside the growing role of private EdTech enterprises, start-ups, and civil society organizations in expanding access to digital education. The study argues that EdTech can become a powerful driver of digital empowerment and inclusive growth only when technological innovation is complemented by equitable policy interventions, localized learning content, teacher capacity-building, affordable internet connectivity, and community-centred digital ecosystems. The paper concludes by proposing policy recommendations for strengthening India’s digital education architecture to ensure that the benefits of technological transformation reach marginalized and rural populations, thereby contributing to educational justice, human capital development, and the realization of Viksit Bharat@2047.